DEEDS : Documents of Early England Data Set - University of Toronto - Library (2013)
"The University of Toronto DEEDS (Documents of Early England Data Set) Research Project was founded in 1975 by Michael Gervers, professor of History of the University of Toronto, to create a database of information culled from medieval property exchange documents which would be of interest to social and economic historians. The DEEDS corpus, as of March 2016, consisted of 44,400 medieval charters. 41,000 of the charters are in Latin. The charters are from the British Isles, France and german-speaking Europe. Additional medieval charters are being added continuously." [self-description]